Biomechanical but not strength or performance measures differentiate male athletes who experience ACL reinjury on return to level 1 sports - King, E.; Richter, C.; Daniels, K. A. J.; Franklyn-Miller, A.; Falvey, E.; Myer, G. D.; Jackson, M.; Moran, M.; Strike, S. (The American Journal of Sports Medicine, 2021)
Background: Performance measures such as strength, jump height/length, and change of direction (CoD) time during anterior cruciate ligament (ACL) rehabilitation have been used to determine readiness to return to play and identify those who may be at risk of rerupture. However, athletes may reach these criteria despite ongoing biomechanical deficits when performing these tests. Combining return-to-play criteria with an assessment of movement through 3-dimensional (3D) biomechanics in male field sports athletes to identify risk factors for ACL rerupture has not been explored previously.